2018
DOI: 10.1515/jpem-2018-0125
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents with premenstrual syndrome: not only what you eat but also how you eat matters!

Abstract: BackgroundCurrent literature suggests that diet is involved in either the development of premenstrual syndrome (PMS) or contributes to symptom severity, but to date, there are no studies evaluating eating attitudes of adolescents with PMS. The aim of this study was to evaluate dietary intake and eating attitudes in adolescents with PMS.MethodsThis study was conducted with 383 adolescents (214 with and 169 without PMS), aged 13–19 years. PMS was diagnosed using the premenstrual syndrome scale (PMSS). The Food F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 34 publications
1
8
0
2
Order By: Relevance
“…Finally, more serious eating attitude problems were found to be associated with higher levels of PMS, and eating attitude problems were thus identi ed as the third determinant of PMS level. This nding is in line with that of a previous study in which eating attitude problems-measured with EAT-26, the same tool used in this study-were observed more frequently in adolescents with PMS than in those without it [52].…”
Section: Discussionsupporting
confidence: 93%
“…Finally, more serious eating attitude problems were found to be associated with higher levels of PMS, and eating attitude problems were thus identi ed as the third determinant of PMS level. This nding is in line with that of a previous study in which eating attitude problems-measured with EAT-26, the same tool used in this study-were observed more frequently in adolescents with PMS than in those without it [52].…”
Section: Discussionsupporting
confidence: 93%
“…The incidence of PMS among students participating in the study was determined as 58.1%. A study by Kaya and Gölbaşı 9 of university students in Turkey found the prevalence of PMS was 33%, while it was found to be 58.1% by Acikgoz et al, 22 55% by Isgin‐Atici et al, 23 58.1% by Topatan and Kahraman, 15 61.6% by Işgın et al, 24 63.7% by Dönmez and Gümüşsoy, 10 and 73.4% by Uzuner and Koçak 8 . A study by Shamnani et al 25 of university students in India found the prevalence was 65%, while Shehadeh and Hamdan‐Mansour 26 reported 92.3% in Jordan, Cheng et al 27 reported 39.85% in Taiwan, and Majeed et al 28 found 80.6% in a study in Pakistan.…”
Section: Discussionmentioning
confidence: 97%
“…Anxiety, changes in appetite, pain and fatigue subscales did not have significant effect on sleep quality (p > .05).4 | DISCUSSIONThe incidence of PMS among students participating in the study was determined as 58.1%. A study by Kaya and Gölbaşı 9 of university students in Turkey found the prevalence of PMS was 33%, while it was found to be 58.1% by Acikgoz et al,22 55% by Isgin-Atici et al,23 58.1% by Topatan and Kahraman,15 61.6% by Işgın et al,24 63.7% by Dönmez and Gümüşsoy,10 and 73.4% by Uzuner and Koçak 8. A study by Shamnani et al25 of university students in India found the T A B L E 4 Correlations between PSQI and PMSS and its subscales.…”
mentioning
confidence: 95%
“…The data used in the present study were obtained from a broad case‐control study in which the relationship between nutritional status, eating attitudes, and the presence/severity of PMS in adolescents were surveyed . Data were collected from female students aged 13–18 years at a high‐school setting in Ankara, Turkey, between September 2013 and September 2014, and processed between September 2014 and April 2015.…”
Section: Methodsmentioning
confidence: 99%